Risk factors of early childhood caries among preschool children in Shanghai, China: a longitudinal study - Yating Xu; Minyi Xu; Weihua Zhang; Xiping Feng; Jingyu Zhan; Yu Zhang; Xi Chen (Frontiers in Oral Health)
IntroductionEarly childhood caries(ECC) has caused a growing public health burden worldwide, but there still remains a gap in the understanding of ECC in Shanghai, China. This study aims to investigate the current profile of ECC and related risk factors of new-onset caries among preschool children in Shanghai, China.Materials and methodsChildren aged 3–5 were included in this two-year longitudinal study from Shanghai. Oral health information and related factors were collected through clinical examinations and questionnaires. Logistic and general linear regression were used to investigate the risk factors of early childhood caries. Ethical approval and informed consent form were achieved in the study.ResultsA total of 192 children completed this 2-year longitudinal study with a follow-up rate of 80.0%. At follow-up, 70.8% of children developed new caries. The study revealed that children with lower mother's education level (p = 0.022), less father's income (p = 0.023), more frequent sugar intake (p = 0.006), and poor oral hygiene (p = 0.012) were more likely to develop new caries. Additionally, general linear regression demonstrated that children who did not use fluoride toothpaste (p = 0.006), those who consumed candy more (p = 0.028), and those with poor oral hygiene (p = 0.001) exhibited greater incremental caries.ConclusionLower father's income, lower mother's education level, frequent sugar consumption, non-use of fluoridated toothpaste, and poor oral hygiene status emerged as significant independent risk factors for ECC.